A Study on Non-Compliance by Work Package Contractor at RTS Link Project - Mohd Farid, Marsya Fakhira; Abdul Razak, Amir Haziq (Progress in Engineering Application and Technology, 2025)
The construction industry in Malaysia has experienced significant growth, benefiting both the sector and the economy. However, it remains one of the most hazardous industries, with high rates of accidents, injuries and fatalities, as highlighted by recent statistics from the Department of Occupational Safety and Health (DOSH) Malaysia. Addressing these safety concerns and improving the safety is crucial to protect workers and enhancing overall productivity. This study aims to identify the most prevalent non-compliance by contractor and analyses the factors contributing to non-compliance. The data collected from Corrective Action Requests (CARs) issued and the number of findings during Safety, Health and Environment (SHE) site inspections will be analysed. For the literature review, it will be used to support the objectives of analysing the contributing factors of contractor non-compliance. The research also seeks to understand these factors and gather perspectives on improving the implementation of safety practices to enhance safety compliance. The study also proposes control measures to address these non-compliance issues, ultimately enhancing safety standards at the construction site.